Mi Instan Gluten Free Kaya Serat Pangan Berbasis Tepung Komposit Mocaf Dan Tepung Talas (Xantosoma L.) - Supartini, Putu; Sri Wiadnyani, Anak Agung Istri; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i03.p08, 2023)
Instant noodles are generally made used wheat flour. The use of wheat in the manufacture of noodles can be replaced with mocaf and taro flour. This research aimed to determine the effect of the comparison of mocaf and taro flour on the characteristics of instant noodles gluten-free so as to obtain the best results. This research used a Complete Randomized Design with 6 levels ratio of composite flour of mocaf and taro flour: 100:0, 90:10, 80:20, 70:30, 60:40, 50:50. Each treatment was repeated 3 times so obtain 18 experimental units. The data obtained were analyzed using analysis of variance and if the treatment had an significant effect on the test parameters, then continued with the Duncan Multiple Range Test (DMRT). The results of the research showed that the comparison of mocaf composite flour and taro flour had a significant effect on water content, elongation, tensile strength, cooking loss, water absorption, hedonic taste, and hedonic overall acceptance. The best treatment in this research is the ratio of mocaf composite flour and taro flour of 60:40. With a characteristic water content 10,18%, optimum time of ripening 236 second, texture 2,37 N, elongation 29,64%, tensile strength 0,026 Mpa, cooking loss 14,51%, dan water absorption 98,91%, ash content 2,76%, fat content 3,57%, protein content 4,15%, carbohydrates 79,34%, and dietary fiber 7,62%, as well as texture assessment, namely slightly chewy and somewhat like, color slightly like, aroma like, taste normal, and overall rating somewhat like.